Hysteresis Current Control Technique of VSI for Compensation of Grid-Connected Unbalanced Loads - Pouresmaeil, Edris; Akorede, Mudathir Funsho; Montesinos-Miracle, Daniel; Gomis-Bellmunt, Oriol; Trujillo Caballero, Juan Carlos (Springer, 2014)
The global trends nowadays in the power generation industry are to supplement the electricity production using distributed generation (DG) technologies based on renewable energy resources such as photovoltaic, wind power, etc. However, failure to properly control the operation of distributed energy resources as they connect to the exiting power grid could provoke many power quality problems on the grid side. For this reason, due considerations must be given to power generation and safe running before DG units is actually integrated into the power grid. The main aim of this paper is to address the grid interconnection issues that usually arise as DG units connect to the electric grid. The proposed strategy, implemented in Matlab/Simulink environment in different operating scenarios, provides compensation for active, reactive, unbalanced, and harmonic current components of grid-connected nonlinear unbalanced loads. The simulation results obtained in this study demonstrate the level of accuracy of the proposed technique, which ensure a balance in the overall grid phase currents, injection of maximum available power from DG resources to the grid, improvement of the utility grid power factor, and a reduction in the total harmonic distortion of grid currents.